Wkład rodzin Dembińskich herbu Rawicz i Nieczuja w rozwój przemysłu w dobrach ziemskich Przysucha w XIX wieku - Zarychta-Wójcicka, Agnieszka (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2010)
The Dembiński family were the owners of acres in Przysucha in Opoczno country. They contributed considerably to the development of ore mining and metallurgy in this area. They found the wire and sword manufactory, gunnery and blast furnace followed by the iron processing factory and metal rolling mill. The most famous member of the Dembiński – Urszula nee Morsztyn Dembińska persisted in searching for new outlets, broadening the range of distributed goods and employing the best agents and merchant as well as running business on a large-scale. The partion of Poland, the inflow of cheap Russian iron and expansive production process based on charcoal caused the collapse of iron production. Due to wrong investments, administration errors and lack of professional supervision Przysucha was no longer one of the most essential iron and weapon industry centre. The glorious era of Przysucha came eventually to an and with the cancellation of town privileges and the outflow of town funds used by the new members of the Dembiński family for military purposes in foreign countries.